"Caracterización microbianas en ensilajes de pasto saboya (Panicum maximum) con la inclusión de cascaras de piñas (Ananas comosus), maracuyá (passiflora edulis) y plátano (Musa AAB)" - Cedeño Loja, Pedro Darío (2016)
The research was conducted at the Laboratorio de Rumiología y Metabolismo Nutricional located at the Experimental Farm "La Maria" Universidad Técnica Estatal de Quevedo (UTEQ), aimed to establish the microbial characteristics of silage saboya grass (Panicum maximum) (PS) associated with agricultural residues pineapple (CP), passion fruit (CM) and banana (CPL). The experimental silos (PVC capacity of 3 kg) were used in a completely randomized design with four replications.The variables evaluated were: total bacteria, lactic acid bacteria, fungi and yeasts. The inclusion of agricultural residues did not influence (P> 0.05) in the content of total bacteria in saboya grass silage cutting 30 days. The highest content (P <0.05) bacteria Lactic acid was introduced in the silage including pineapple peel (T2) and passion fruit (T3) attributable to soluble carbohydrate content of these wastes. Silage without including agricultural residues (T1) reported the highest (P <0.05) proliferation of fungi showing lower efficiency of conservation. The proliferation of yeast in a similar effect among all silages including the control (P> 0.05), reporting lower values indicating better preservation stability was found. Keywords: Grass, silage, bacteria, pineapple, passion fruit and banana.